2014
DOI: 10.1371/journal.pone.0084916
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression Analysis of Diapause Hormone and Pheromone Biosynthesis Activating Neuropeptide (DH-PBAN) in the Legume Pod Borer, Maruca vitrata Fabricius

Abstract: Neuropeptides play essential roles in a variety of physiological responses that contribute to the development and reproduction of insects. Both the diapause hormone (DH) and pheromone biosynthesis activating neuropeptide (PBAN) belong to the PBAN/pyrokinin neuropeptide family, which has a conserved pentapeptide motif FXPRL at the C-terminus. We identified the full-length cDNA encoding DH-PBAN in Maruca vitrata, a major lepidopteran pest of leguminous crops. The open reading frame of Marvi-DH-PBAN is 591 bp in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 81 publications
2
27
1
Order By: Relevance
“…Sequencing of the entire coding sequence and exon–intron boundaries of the Ostnu ‐ PBAN gene revealed that it is at least 5 kb long and consists of six exons and five introns with a conserved distribution of intron positions within codons (0, 2, 1, 2, 1). The Ostnu‐PBAN gene has extensive structural homology to the B. mori (Xu et al ., ), Helicoverpa armigera (Zhang et al ., ), Clostera anastomosis (Jing et al ., ) and M. vitrata (Chang & Ramasamy ) DH ‐ PBAN genes, which have previously been identified in the genomes of lepidopteran species belonging to various families. Short‐ and medium‐length 3′ UTR forms were also observed in the amplification products obtained from adzuki bean borer ( Os.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of the entire coding sequence and exon–intron boundaries of the Ostnu ‐ PBAN gene revealed that it is at least 5 kb long and consists of six exons and five introns with a conserved distribution of intron positions within codons (0, 2, 1, 2, 1). The Ostnu‐PBAN gene has extensive structural homology to the B. mori (Xu et al ., ), Helicoverpa armigera (Zhang et al ., ), Clostera anastomosis (Jing et al ., ) and M. vitrata (Chang & Ramasamy ) DH ‐ PBAN genes, which have previously been identified in the genomes of lepidopteran species belonging to various families. Short‐ and medium‐length 3′ UTR forms were also observed in the amplification products obtained from adzuki bean borer ( Os.…”
Section: Discussionmentioning
confidence: 99%
“…The total DNA was extracted from individual larva of Maruca using (Chang & Srinivasan, 2014) using Primer3 (Untergasser et al, 2007), and their quality was checked in PCR Primer Stats (http://www.bioin forma tics.org/sms2/ Alternative primer 5′-GTTGCAGGAGCTGAAAATGG-3′ 5′-GCTGTCCTTCGGGTAACATC-3′ Internal primer 5′-CTC ATC TGC ATG TCC ACC A -3′ 5′-CTT GGT GGA CAT CCA GAT GAG-3′ PBP2 Main primer 5′-AATGGCCTAAAGGGCCACAA-3′ 5′-AGGTTTCATGTCACAATCTTCATC-3′ 1.1-3.0…”
Section: Dna Extractionmentioning
confidence: 99%
“…This has resulted in confusion over which conserved domains are present among non-lepidopteran species, and how to apply the a, b, PBAN and c NP labels. While we have adopted the format of Jurenka and Nusawardani (2011), other examples of PBAN-like peptide classifications exist in the literature (Choi et al, 2010;2013;Chang and Ramasamy, 2014). Thus, a class-wide pk/pban translation analysis is needed to identify which conserved peptide domains are present, regardless of functional processing, thereby making it possible to reliably identify NP products.…”
Section: Pk/pban Gene Structure and Homologymentioning
confidence: 99%